HOW BRAND EMPATHY CREATED: STUDY ON ORGANIC VIRAL CONTENT - Pramesthi, Jasmine Alya; Priastuty, Chairunnisa Widya (Universitas Pendidikan Nasional, 2024)
This research explores and develops the concept of Brand Empathy which includes cognitive empathy, emotive empathy, and empathic action, in the context of viral content between Indomie and Mie Gaga on the TikTok platform, generated through AI storytelling. This research describes the empathy formed by significant discussions on social media, especially TikTok, regarding the story of Djajadi Djaja, the founder of Mie Gaga, and the journey of establishing the instant noodle brand. The research method uses qualitative content analysis with snowball sampling through social media content and comments on TikTok, Instagram, and Twitter. Positive and negative opinions play an important role in shaping Brand Empathy. With AI storytelling technology, viral content triggers intense reactions and leads consumers to Brand Empathy. The development of Brand Empathy involves cognitive empathy in understanding and identifying controversies, emotive empathy in emotional responses, and empathic action in tangible actions. The emotional attachment between the audience and the brand creates a parasocial relationship, which demonstrates consumer loyalty and brand reputation. This research provides deep insight into the complexity of e-WOM and introduces a new approach to understanding audience-brand interactions in the digital age through Brand Empathy. This research also highlights the role of cognitive empathy in Brand Empathy related to information dissemination, especially in the context of viral content about Mie Gaga and Indomie. Audiences actively understood and identified feelings, thoughts and perspectives related to the controversy.